A Comprehensive Review on Cryptography Algorithms: Methods and Comparative Analysis - Donia Fadil Chalob,; Rusul Hussein Hasan,; Suaad M. Saber, (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The evolution of cryptography has been crucial to preservation subtle information in the digital age. From early cipher algorithms implemented in earliest societies to recent cryptography methods, cryptography has developed alongside developments in computing field. The growing in cyber threats and the increase of comprehensive digital communications have highlighted the significance of selecting effective and robust cryptographic techniques. This article reviews various cryptography algorithms, containing symmetric key and asymmetric key cryptography, via evaluating them according to security asset, complexity, and execution speed. The main outcomes demonstrate the growing trust on elliptic curve cryptography outstanding its capability and small size, while highlighting the requirement for study in the post-quantum cryptographic field to address the threats rising from quantum computing. The comparative analysis shows a comprehensive understanding that combines classical cryptography algorithms with up-to-date approaches such as chaotic-based system and post-quantum cryptography, confirming that the study addresses the future of cryptography security in the aspect of emerging challenge like quantum computing.
Keywords: Symmetric Key; Asymmetric Key; Post-Quantum Cryptography; Chaos-Based Systems